Lightning Shoes Enterprise : Smart Charging Shoes / Muhamad Aliff Onn ...[et al.] - Onn, Muhamd Aliff; Harrun, Muhammad Hamizan; Zaharullah, Muhammad Irsyad Al Munzir; Hazian, Muhammad Firdaus; Mohd Hatta, Muhammad Azhim (2016)
Our product was named as lightning shoes because it can generates its own energy by using piezoelectric devices. This devices was use as converter that can convert the kinetic energy to the electrical energy and stored it on capacitor that been located on this shoes.